Randomized, controlled pilot trial of solifenacin succinate for overactive bladder in Parkinson's disease. Issue 5 (May 2015) - Zesiewicz, Theresa A.; Evatt, Marian; Vaughan, Camille P.; Jahan, Israt; Singer, Carlos; Ordorica, Raul; Salemi, Jason L.; Shaw, Jessica D.; Sullivan, Kelly L.; Non-Motor Working Group of the Parkinson Study Group (PSG)
Abstract Objective To evaluate the efficacy of solifenacin succinate in Parkinson's disease (PD) patients suffering from overactive bladder (OAB). Background Urinary dysfunction is a commonly encountered non-motor feature in PD that significantly impacts patient quality of life. Design/methods This was a double-blind, randomized, placebo-controlled, 3-site study with an open label extension phase to determine the efficacy of solifenacin succinate in idiopathic PD patients with OAB. Patients were randomized to receive solifenacin succinate 5–10 mg daily or placebo for 12 weeks followed by an 8-week open label extension. The primary outcome measure was the change in the mean number of micturitions per 24 h period. Secondary outcome measures included the change in the mean number of urinary incontinence episodes and the mean number of nocturia episodes. Results Twenty-three patients were randomized in the study. There was no significant improvement in the primary outcome measure in the double-blind phase, but there was an improvement in the number of micturitions per 24 h period in the solifenacin succinate group compared to placebo at a mean dose of 6 mg/day (p = 0.01). In the open label phase, the mean number of urinary incontinence episodes per 24 h period decreased (p = 0.03), as did the number of nocturia episodes per 24 h period (p = 0.01). Adverse events included constipation and xerostomia, which resolved after treatment was discontinued. Conclusions In this pilot trial, solifenacin succinate treatment led to an improvement in urinary incontinence, despite persistence in other OAB symptoms.